Thiophosphinoyl‐Tethered Ylide‐Substituted Heavier Carbenes: Synthesis, Structures and Stabilities. Issue 24 (17th March 2023) - Jörges, Mike; Gauld, Richard M.; Steinert, Henning; Kelling, Leif; Swamy, V. S. V. S. N.; Kroll, Alexander; Mallick, Bert; Gessner, Viktoria H.
Abstract: The synthesis and structure analysis of a series of mono and diylide‐substituted tetrylenes of type YEX and Y2 E (E=Ge, Sn, Pb; X=Cl or Br) using a thiophosphinoyl‐tethered metallated ylide (Y=Ph2 P(S)−C−P(pip)Ph2 with pip=piperidyl) is reported, amongst the first ylide‐substituted plumbylenes. The tetrylenes feature distinct trends in the spectroscopic and structural properties of the ylide ligand with increasing atomic number of the tetrel element. For instance, an increasingly high‐field shifted signal for the thiophosphinoyl group is observed in the 31 P{ 1 H} NMR spectrum as a consequence of the increasing polarity of the element‐carbon bond, which likewise results in a shortening of the ylidic C−P bond in the solid‐state structure. The diylidyltetrylenes are unstable towards transylidation forming the mono(ylide)tetrylenes when treated with the tetrel dihalides according to the stability trend: Y2 Pb <Y2 Sn <Y2 Ge <YPbBr <YSnCl <YGeCl . Starting from the monoylide‐substituted chlorotertrylenes the first unsymmetrical diylidyltetrylenes of type YEY' can be accessed, whose solid‐state structures revealed that not the C−E but the S−E bond to the thiophosphinoyl group is most affected by the second ylide substituent. Abstract : The synthesis and structure analysis of a series of mono and diylide‐substituted tetrylenes of type YEX and Y2 E (E=Ge, Sn, Pb; X=Cl or Br) with a thiophosphosphinoyl‐tethered ylide is reported. Their relative stabilities were determined by ylide transfer reactions and the first unsymmetrical heavier diylidylcarbenes accessed from chloro(ylidyl)tetrylenes.